IDENTIFIKASI POLIFENOL PADA KULTUR IN VITRO KALUS Camellia sinensis UNTUK BAHAN MINUMAN FUNGSIONAL - Basuki, Sutini (UPN VETERAN JAWA TIMUR, 2012)
Polyfenol included secondary bioactive metabolite had a function to reduce degenerative syndrome. Polyfenol contained in tea act as bioactive syntesis from hydroksil part and could be act as functional drinking and control human organ as biological metabolism. Problem in gain polyfenol productfrom tea plantation / camellia sinensis L for intance : depent on season, need a large area for cultivication, and low contain for productivity.For thesepurpose there were main idea to ncrease polyfenol productivity by mean of in vitro culture technique. These technique could reduce all problem above. The main purpose of these research were to find production technique by mean callus culture. Method to gain the purose were : (1) callus induction by cultify part of tea leaves in many variance grown culture , (2) Sub culture callus using same culture media as callus induction (3) Morphologycal check for callus (4) Kualitative analisys callus polyfenol.Result of these research were callus with hand time retention (tR) on High Performace Liquid Chromatography for 14 minutes with a same time of standart poyfenol. Polyfenol had potential to support the retention of functional beverage.Key words : Polyphenols, in vitro culture of callus , Camellia sinensis